The development of a psychosocial intervention that supports siblings of children and adolescents with serious chronic health conditions in Aotearoa New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Clinical Psychology at Massey University - Armstrong, Kathleen (Massey University, 2024)
Due to recent advances in medical care, many childhood chronic health conditions (CHCs) are less likely to be fatal and more able to be successfully managed. This has led to an increase in the prevalence of children living with CHCs, which presents the affected child, their parents, and their siblings with significant long-term consequences and challenges. Extant literature points to siblings of children with CHCs being a vulnerable population who are at increased risk of developing depression, anxiety, post-traumatic stress symptoms, lower quality of life, and disruption to academic and social functioning. Consequently, there have been calls for the development of sibling support services both in Aotearoa New Zealand (New Zealand) and internationally. Recent needs-based research on siblings of children with cancer and other serious CHCs in New Zealand reported critical unmet needs across the following domains: Information about the illness; Dealing with feelings; Time out and recreation; Support from friends and other young people; Understanding from their family; and Relationship with their affected sibling. These findings emphasise the necessity of a nationwide intervention that provides siblings with support close to the time of their brother’s or sister’s diagnosis. The aim of the present study was to develop a needs-based psychosocial intervention for siblings of children with serious CHCs, which protects and promotes the health and wellbeing of this vulnerable population and recognises their existing individual and familial strengths. A literature review was conducted to investigate the impact serious childhood CHCs have on siblings, and to establish whether the commonalities in sibling experiences justify taking a transdiagnostic approach in the development of a sibling intervention. This was followed by a systematised review of existing sibling interventions and an evaluation of their efficacy. Informed by the two major reviews and existing needs-based sibling research, a manualised intervention was developed to meet the self-reported unmet needs of siblings, using a combination of evidence-based therapeutic modalities.
Keywords: chronic health conditions, siblings, interventions; Chronic diseases in children; Patients; Chronically ill children; Family relationships; New Zealand; Siblings; Psychological aspects; Services for; 520302 Clinical psychology